2019
DOI: 10.1111/jzo.12743
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal mechanisms of coexistence in an European mammal community in a protected area of southern Italy

Abstract: Assessing the spatiotemporal overlap amongst animal species living in sympatry helps to shed light on mechanisms of interspecific coexistence. We analysed the spatiotemporal coexistence in a predator–prey system through multiyear camera trapping, in a mountainous protected area of southern Italy (January 2012–January 2017). Temporal activity patterns and their interspecific overlap, as well as spatial overlap, were estimated for a top predator, that is the wolf Canis lupus, three species of wild ungulates, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 87 publications
12
69
1
Order By: Relevance
“…In contrast to other studies (e.g. Mori et al 2020), spatial partitioning did not seem to play a major role in structuring interspecific coexistence in our study system. It is worth noting that the study area is fenced and surrounded by a territory strongly affected by human presence as it is located in the suburbs of the largest city in Italy (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to other studies (e.g. Mori et al 2020), spatial partitioning did not seem to play a major role in structuring interspecific coexistence in our study system. It is worth noting that the study area is fenced and surrounded by a territory strongly affected by human presence as it is located in the suburbs of the largest city in Italy (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, our results showed a high temporal overlap among the three species during all seasons. This is consistent with the findings of Mori et al (2020), which pointed at a high temporal overlap among ungulates species, particularly between wild boar and roe deer. It is interesting to note that, despite the high temporal overlap of activity among the studied species, our results showed that during autumn, winter and spring, roe deer and fallow deer had a peak of activity at dawn, when wild boar was less active.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This would also reflect the nocturnal behaviour of the coypu in its native range (Palomares et al 1994 ), where a number of potential predators occurs (e.g., the jaguar Panthera onca , the puma Puma concolor , the ocelot Leopardus pardalis , the oncilla L. tigrinus and six species of grey foxes Lycalopex spp.). Despite most predators being nocturnal in Europe (Mori et al 2020b ), which may suggest an increase in encounter rate with nocturnal coypus, this large rodent has also shown another temporal adaptation.…”
Section: Discussionmentioning
confidence: 99%